Issues and topics to consider for information management research in eMedia industries - Stockleben, B.; Lugmayr, Artur (International Ambient Media Association (iAMEA), 2013)
The digital media industry produces vast data along the content value chain. Any interaction with digital media yields data, often in real-time, both on production and consumption side. This data can be turned to immediately available business information on the operational level, e.g. editors continuously tweak their workflows upon social media feedback. This questions the traditional distinction between organization levels, changing the role of strategic management in the media business and the kind of information it is acting upon. An integration of business information and content management systems throughout the whole value chain holds great potential for future business intelligence applications in the media sector.